Empowerment of Disabled Groups through the Application of Aquaponic Livestock Technology - Yohanis Umbu Laiya Sobang; Chaterina Agusta Paulus; Magdarita Riwu; Fredeicus Dedy Samba (Universitas Pendidikan Ganesha, 2025)
People with disabilities often experience limited access to decent work and supporting technology, resulting in low income and vulnerability to family food security. This condition reflects the importance of technology-based economic empowerment interventions that are environmentally friendly and easy to adopt. This community service aims to analyze the effectiveness of the application of aquaponics-animal husbandry technology in improving the competence, productivity, and potential for economic independence of people with disabilities. This community service uses a qualitative approach with a Participatory Rural Appraisal (PRA) design. The subjects were 58 residents with disabilities, who also became subjects of the training and technology application trial. Data were collected through pre- and post-tests of competency, direct observation, and field documentation, with instruments in the form of skill assessment sheets and open-ended interviews. Data analysis was conducted descriptively-qualitatively. The results showed an increase in the ability to adopt aquaponics-animal husbandry technology after the training, where 61% successfully completed the production unit independently, while 17.11% were still in the half-finished stage, and only 3.28% did not continue. The potential increase in partner income reached IDR 20,100,000 per year. The conclusion shows that the integration of environmental technologies such as aquaponics-animal husbandry can increase food independence, economics, and life skills of people with disabilities.